Implementation of the Project Based Learning Model to Improve Student Learning Outcomes in Class X Basic Electromechanical Work at Vocational School - Ridwan Ridwan; Melyanti Tinggogoy; Mutiara Nurmanita (Journal on Education, 2023)
This research aims to determine the implementation of the use of the Project Based Learning learning model in improving the learning process seen from student learning outcomes, especially in the Electromechanical Work subject at the Tondano vocational high school. The research method used in this research was classroom action research carried out in 2 cycles. The research population was students at Vocational High School 3 Tondano, in this case the electrical power installation engineering skills competency and then the research subjects for class X electricity. Based on the research results, it was found that for the first cycle research results, the percentage of student learning completeness was 34.62%, while for the second cycle the percentage was 92.31%. Thus, it can be concluded from this research that it turns out that the application of learning using the Project Based Learning Model can improve student learning outcomes, especially for the Electromechanical Work subject at the Tondano vocational high school.